Study of Living Hadith on the Khataman al-Qur’an Tradition over Graves in North Padang Lawas: Studi Living Hadis Tradisi Khataman al-Qur'an di atas Kuburan di Padang Lawas Utara - Ramadan, Ilham (Jurnal Living Hadis, 2022)
This study aims to describe the tradition of Quranic Khataman in the graveyard preserved by the people of North Padang Lawas. This research uses a qualitative type with a living hadith approach. This research shows that this tradition is a public reception to the hadith relating to the remains of the pilgrims leaving the burial area as well as the reward and prayers from a righteous child to both parents.  There are several hadiths that form the basis of theological references to the implementation of the Quranic khatam tradition. First, the narration of Bukhari's (1252) and (1338). Second, the narration of Muslims (3084) and (1631). There are several important questions that are the focus of research. First, what is the urgency and procedure for carrying out the Khataman Al-Qur'an tradition? Second, how the Study of Living Hadith plays a role in the tradition of khataman al-Qur'an over the grave. The results of this study found the conclusion that the tradition of quranic khatam above the graveyard is the reflection of the understanding of the hadith. and the procedures for its implementation are adapted to the guidance of local clerics and religious leaders.